Caracterização química do óleo do mesocarpo de acessos de Elaeis oleifera (H.B.K.) oriundos da Amazônia Brasileira e mapeamento in silico de lipases putativas das classes 3 (GxSxG) e GDSL nos genomas de palma de óleo - Gutiérrez, Maria Daniela España (2017)
The quality of oil palm is affected by the acidification resulting from the activity of the lipases (triacylglycerol acylhydrolases EC 3.1.1.3), which hydrolyze the triglycerides rapidly liberating free fatty acids (FFA) in the mesocarp of ripe and / or bruised fruits. The objective of this work was to characterize the oil extracted from the mesocarp of fruits of different Caiaué (Elaeis oleifera) accesses from the Brazilian Amazon of the Embrapa Germplasm Active Bank (BAG), through chemical analyzes of the type of oil in base Moisture content, acidity, total carotenoid content, and fatty acid profile. The fruits of Caiaué were submitted to different storage times. This approach allowed to verify that there is phenotypic variability among the most representative accessions of the Caiaué BAG collection, as well as to indirectly assess the action of lipase throughout the storage that occurs before pr ocessing. In this study, it was also made an in silico identification of putative class 3 and GDSL lipases in the two species of the genus Elaeis spp., as possible sources responsible for the acidification of palm oil. This search was done using the public genomic data of E. guineensis EG5 and the private data of E.oleifera "Manicoré" draft (version 1.0 and 2.0) sequenced by Embrapa Agroenergia. Six genes orthologous of the same evolutionary lineage (three in E. guineensis and three in E. oleifera) were detected and characterized structurally. With this, we hope to advance in the future work of marker discovery (SNPs) in these lipases candidates for use in assisted selection of low acid genotypes. Additionally, the results suggest that there is a great diversity of putative lipases of the GDSL class and class 3 (GxSxG) present in the two oil palm species, which can be evaluated to identify lipases related to acidification of oil palm.